Oxalic acid excited calcium silicate mineral cementing material composition and application thereof
By oxalic acid, the calcium silicate mineral cementitious material composition is stimulated, and the problems of unstable carbon dioxide emissions and oxalate cement hydration in cement production are solved, and the effect of extending construction time, improving strength and structural compactness is achieved. It is suitable for low-temperature environments and has environmentally friendly characteristics.
Patent Information
- Application Number
- CN202510078335.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-15
AI Technical Summary
The carbon dioxide emissions are high in the existing cement production process, and the hydration and heat release rate of oxalate cement is too fast, resulting in unstability of the product and decrease in strength.
Oxalic acid is used to stimulate the calcium silicate mineral gelling material composition, and the reaction speed is adjusted, the settling time is extended, and the raw material utilization is improved by adjusting the mass ratio of oxalic acid to calcium silicate minerals and the ratio of retarder.
It extends the construction time of gelled materials, improves the completeness of reaction, enhances the strength and structural compactness of gelled materials, is suitable for low-temperature environments, and has the characteristics of green and environmental protection.
Smart Images

Figure BDA0005247759560000051 
Figure BDA0005247759560000071 
Figure BDA0005247759560000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials and relates to an oxalic acid activated calcium silicate mineral cementitious material and application thereof. Background Art
[0002] Global warming is caused by the increase in anthropogenic greenhouse gas emissions, with carbon dioxide accounting for 66% of all greenhouse gases and the growth rate of carbon dioxide in the past five years accounting for 82% of the total growth rate. The cement industry is one of the key industries for China to achieve carbon neutrality. China's cement production and consumption account for more than half of the global market, and carbon emissions account for 13% of the country's total emissions. Carbon dioxide emissions in the cement production process mainly come from the clinker production process, among which the carbon dioxide emitted by the process of calcining limestone to produce quicklime accounts for about 55-70% of the total carbon emissions of the entire production process; the high-temperature calcination process requires the combustion of fuel, so the carbon dioxide generated accounts for about 25-40% of the total carbon emissions of the entire production process.
[0003] At present, the research on oxalate cement in China mainly focuses on the treatment and recycling of solid waste. Slag-based oxalate cement is a kind of cement prepared by using slag (such as garbage incineration slag, blast furnace slag, etc.) and oxalate as main raw materials or additives. Chinese patent CN 107098612A "A magnesium-based oxalate cement" is an acid-base cement that uses acidic components such as oxalic acid to chemically react with magnesium oxide. Magnesium oxide needs to be reburned at high temperature, and the reaction with oxalic acid is incomplete, with magnesium oxide and oxalic acid remaining. Oxalate acid-base cement releases heat rapidly and heat in large quantities during the reaction process, and the setting speed is too fast; too fast hydration heat release rate makes the hydration product unstable and has many defects, and the strength of the hardened body decreases in the later stage. Summary of the invention
[0004] In view of the problems and shortcomings in the prior art, the object of the present invention is to provide an oxalic acid activated calcium silicate mineral cementitious material and its application.
[0005] To achieve the purpose of the invention, the technical solution adopted by the present invention is as follows:
[0006] The first aspect of the present invention provides an oxalic acid-activated calcium silicate mineral cementitious material composition, comprising the following raw materials: oxalic acid, calcium silicate mineral and retarder, wherein the mass ratio of the oxalic acid to the calcium silicate mineral is (1.2-1.5):1, and the mass ratio of the retarder to oxalic acid is (0-1):(4-5).
[0007] According to the above-mentioned cementitious material composition, preferably, the calcium silicate mineral is at least one of tricalcium disilicate (C3S2), γ-dicalcium silicate (γ-C2S), and calcium silicate (CS). More preferably, the calcium silicate mineral is γ-dicalcium silicate.
[0008] According to the above-mentioned cementitious material composition, preferably, the preparation method of the γ-dicalcium silicate is: silicon dioxide and calcium hydroxide are mixed in a molar ratio of 1:2 and sintered at 1450°C to obtain a sintered material, and the sintered material is ground after cooling to obtain γ-dicalcium silicate; more preferably, the sintering time is 4 hours.
[0009] According to the above-mentioned cementitious material composition, preferably, the preparation method of the tricalcium disilicate is: calcium carbonate and silicon dioxide are mixed in a molar ratio of 3:2 and sintered at 1460°C to obtain a sintered material, and the sintered material is ground after cooling to obtain tricalcium disilicate; more preferably, the sintering time is 1 hour.
[0010] According to the above-mentioned cementitious material composition, preferably, the preparation method of the calcium silicate is: calcium hydroxide and silicon dioxide are mixed in a molar ratio of 1:1 and then sintered at 1420°C to obtain a sintered material, and the sintered material is ground after cooling to obtain calcium silicate; more preferably, the sintering time is 4 hours.
[0011] According to the above-mentioned cementitious material composition, preferably, the oxalic acid is anhydrous oxalic acid and / or hydrated oxalic acid.
[0012] According to the above-mentioned cementitious material composition, preferably, the hydrated oxalic acid is monohydrated oxalic acid and / or dihydrated oxalic acid.
[0013] According to the above-mentioned cementitious material composition, preferably, the retarder is at least one of oxalate, acetic acid and citric acid.
[0014] According to the above-mentioned gelling material composition, preferably, the oxalate is sodium oxalate and / or potassium oxalate; more preferably, the oxalate is sodium oxalate.
[0015] According to the above-mentioned cementitious material composition, preferably, the particle size of the calcium silicate mineral is ≤100 μm, the particle size of the oxalic acid is ≤100 μm; and the particle size of the retarder is ≤100 μm.
[0016] The second aspect of the present invention provides the use of the cementitious material composition described in the first aspect in cementitious materials or concrete.
[0017] The third aspect of the present invention provides a method for using the cementitious material composition of the first aspect, comprising: uniformly mixing water and the cementitious material composition in proportion to obtain a slurry; and subjecting the slurry to molding and curing to obtain a cementitious material solid.
[0018] According to the above-mentioned method of use, preferably, the mass ratio of the water to the cementitious material composition is (0.2-0.4):1; more preferably, the mass ratio of the water to the cementitious material composition is (0.25-0.35):1; most preferably, the mass ratio of the water to the cementitious material composition is 0.3:1.
[0019] According to the above-mentioned method of use, preferably, the temperature of the water is 0°C to 25°C, and the temperature of the curing treatment is 0°C to 25°C.
[0020] According to the above-mentioned method of use, preferably, the curing treatment time is 2 hours.
[0021] A fourth aspect of the present invention provides a cementitious material, wherein the cementitious material comprises the cementitious material composition described in the first aspect.
[0022] A fifth aspect of the present invention provides a concrete material, wherein the concrete material comprises the cementitious material composition according to the first aspect.
[0023] According to the above concrete material, preferably, the concrete material further comprises aggregate and a water reducing agent.
[0024] The principle of preparing oxalic acid activated calcium silicate mineral cementitious material of the present invention is:
[0025] The oxalic acid in the present invention can dissolve in water to produce C2O4 2- ions, reacting with calcium silicate minerals and H2O in the system (C2O4 2- +Ca 2+ +H2O=CaC2O4·H2O,C2O4 2- +Ca 2+ +2H2O=CaC2O4·2H2O), the CaC2O4·H2O / CaC2O4·2H2O precipitates generated by the reaction are adhered to each other. In addition, a certain amount of gel can be formed to provide strength for the entire gelling material system.
[0026] Compared with the prior art, the present invention has the following positive and beneficial effects:
[0027] (1) Conventional cement generally has high hydration activity, and the hydration reaction process is exothermic. When oxalic acid and water are added to conventional cement, the reaction between oxalic acid and cement is very rapid and extremely violent, the water evaporates quickly, and the cement is quickly solidified and cannot be stirred into shape. The present invention uses a calcium silicate mineral (including tricalcium disilicate, γ-dicalcium silicate, and calcium silicate) with ultra-low hydration activity in combination with oxalic acid and a retarder to prepare a cementitious material composition. When the cementitious material composition is in contact with water, the calcium silicate mineral has an ultra-low hydration activity, and the silicate mineral hardly undergoes a hydration reaction with water to release heat, so the setting time of the cementitious material can be extended, thereby extending the construction time of the cementitious material. At the same time, the completeness of the reaction between oxalic acid and the calcium silicate mineral can be improved, thereby improving the utilization rate of raw materials.
[0028] (2) The oxalic acid-activated calcium silicate mineral cementitious material of the present invention adjusts the ion dissolution rate and migration rate by adjusting the ratio of retarder to oxalic acid, water temperature and curing temperature, thereby adjusting the reaction speed, so that the setting time of the cementitious material can be adjusted according to actual construction needs.
[0029] (3) The method of using the oxalic acid-activated calcium silicate mineral cementitious material composition of the present invention is similar to that of conventional cement materials and is simple to operate; at the same time, the calcium silicate mineral reacts with oxalic acid to generate calcium oxalate as an insoluble salt, which gives the cementitious material a certain strength.
[0030] (4) The oxalic acid-activated calcium silicate mineral cementitious material composition of the present invention can react to generate gel after contact with water. Compared with the chemical complex product of general acid-base cement, the gel product can fill the pores of the cementitious material, thereby enhancing the toughness of the prepared cementitious material and improving the structural density of the prepared cementitious material, thereby improving the strength of the cementitious material. The strength of the cementitious material prepared using the cementitious material composition of the present invention is greatly improved compared with that of magnesium oxalate acid-base cement; at the same time, the presence of the gel product can slow down the diffusion rate, thereby prolonging the setting time of the cementitious material, providing sufficient time for the construction of the cementitious material.
[0031] (5) The oxalic acid-activated calcium silicate mineral cementitious material composition described in the present invention is suitable for low-temperature environments, still has good reaction activity at low temperatures, and has a mild reaction and high strength after coagulation, wherein the 7-day compressive strength can reach 49.1 MPa, and the 28-day compressive strength can reach 55.5 MPa; therefore, the oxalic acid-activated calcium silicate mineral cementitious material composition described in the present invention can be widely used in concrete pavement maintenance, construction in high-cold and low-temperature areas, etc.
[0032] (6) The oxalic acid-activated calcium silicate mineral cementitious material described in the present invention is green and environmentally friendly, will not cause environmental pollution, and has broad application prospects in various scenarios such as green building materials and construction. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a photo of the appearance of the gelling material P1 sample prepared in Example 1;
[0034] Figure 2 The XRD diagram of the gelling material P1 prepared in Example 1; in the diagram: 1 is the diffraction peak of calcium oxalate monohydrate (CaC2O4·H2O), and 2 is the diffraction peak of calcium oxalate dihydrate (CaC2O4·2H2O);
[0035] Figure 3 These are SEM images of the gelling material P1 prepared in Example 1; (a) is a SEM image at 3000 times magnification, and (b) is a SEM image at 30000 times magnification. DETAILED DESCRIPTION
[0036] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0037] The following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0038] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. When the terms "comprise" and / or "include" are used in this specification, it indicates that there are features, steps, operations, parts and / or combinations thereof.
[0039] The experimental methods in the following examples without specifying specific conditions all adopt conventional techniques in the art or follow the conditions recommended by the manufacturers; the reagents or instruments used without specifying the manufacturers are all conventional products that can be obtained commercially.
[0040] Example 1: Discussion on types of calcium silicate minerals
[0041] In order to study the influence of the type of calcium silicate mineral on the properties of the prepared cementitious material, the present invention carried out Examples 1-1 to 1-4. The specific contents of Examples 1-1 to 1-4 are as follows:
[0042] Example 1-1:
[0043] An oxalic acid-activated calcium silicate mineral cementitious material composition, consisting of oxalic acid dihydrate (48g), a calcium silicate mineral (40g) and a retarder (12g); wherein the mass ratio of the oxalic acid dihydrate to the calcium silicate mineral is 1.2:1, the particle size of the oxalic acid dihydrate is less than 100μm, and the calcium silicate mineral is γ-dicalcium silicate (particle size less than 100μm); the mass ratio of the retarder to the oxalic acid dihydrate is 1:4, the particle size of the retarder is less than 100μm, and the retarder is sodium oxalate.
[0044] The preparation method of the gamma-dicalcium silicate is as follows: silicon dioxide and calcium hydroxide are mixed in a molar ratio of 1:2, and then sintered at 1450° C. for 4 hours to obtain a sintered material; the sintered material is cooled and then ball-milled to obtain gamma-dicalcium silicate with a particle size of less than 100 μm.
[0045] The preparation method of the oxalic acid activated calcium silicate mineral cementitious material composition is as follows: weigh oxalic acid, calcium silicate mineral and retarder, and mix them evenly to obtain the oxalic acid activated calcium silicate mineral cementitious material composition.
[0046] Embodiment 1-2:
[0047] Example 1-2 is substantially the same as Example 1-1, except that the calcium silicate mineral is tricalcium disilicate.
[0048] The preparation method of tricalcium disilicate is as follows: calcium carbonate and silicon dioxide are mixed in a molar ratio of 3:2, and then sintered at 1460° C. for 1 hour to obtain a sintered material; the sintered material is cooled and then ball-milled to obtain tricalcium disilicate with a particle size of less than 100 μm.
[0049] Embodiment 1-3:
[0050] Example 1-3 is substantially the same as Example 1-1, except that the calcium silicate mineral is calcium silicate.
[0051] The preparation method of the calcium silicate is as follows: calcium hydroxide and silicon dioxide are mixed in a molar ratio of 1:1, and then sintered at 1420° C. for 4 hours to obtain a sintered material; the sintered material is cooled and then ball-milled to obtain calcium silicate with a particle size of less than 100 μm.
[0052] Embodiment 1-4:
[0053] Example 1-4 is basically the same as Example 1-1, except that the calcium silicate mineral is silicate cement (taking PC42.5 cement as an example).
[0054] In order to study the performance of the oxalic acid-activated calcium silicate mineral cementitious material compositions prepared in Examples 1-1 to 1-4, the oxalic acid-activated calcium silicate mineral cementitious material compositions prepared in Examples 1-1 to 1-4 were used to prepare cementitious materials, and the obtained cementitious materials were respectively recorded as cementitious material P1, cementitious material P2, cementitious material P3, and cementitious material P4, and the performance of cementitious materials P1 to P4 were tested.
[0055] The preparation method of the cementitious material is as follows: add 0°C water to the cementitious material composition, the mass ratio of water to the cementitious material composition is 0.3:1, stir and mix to obtain slurry, pour the slurry into a 20mm*20mm*20mm six-piece mold, vibrate on a vibration table for 30s to form, scrape the upper part flat, put it into a curing box for constant temperature curing at 25°C, and obtain the cementitious material. The setting time is calculated from the start time of the cementitious material molding to the hardening of the cementitious material. According to GB / T 50081-2019 standard, the mechanical properties of the cementitious material after 5 hours, 10 hours, 1 day, 3 days, 7 days, and 28 days of coagulation are tested using a pressure testing machine. The test results of cementitious materials P1 to P4 are shown in Table 1.
[0056] Table 1 Effect of calcium silicate mineral types on the properties of cementitious materials
[0057]
[0058] As shown in Table 1, the setting time and compressive strength of the prepared cementitious materials are significantly different for different types of calcium silicate minerals; when the calcium silicate mineral is PC42.5 cement, the moment water is added to the cementitious material composition, the reaction is very rapid, the mixed system quickly releases heat and produces water vapor, the water evaporates quickly, and the slurry cannot be stirred and formed when the water is completely lost. Therefore, it is not suitable for preparing cementitious materials. When the calcium silicate mineral is calcium silicate, the shortest setting time of the cementitious material is 22.3 minutes, and the 7d compressive strength of the cementitious material reaches 36.5MPa; when the calcium silicate mineral is tricalcium disilicate, the setting time of the cementitious material is extended and the compressive strength is also improved; when the calcium silicate mineral is γ-dicalcium silicate, the longest setting time of the cementitious material is 32.6min, and the compressive strength of the cementitious material also reaches the highest (45.4MPa). Therefore, in the actual construction process, the calcium silicate mineral can be reasonably selected according to the setting time and strength requirements of the cementitious material.
[0059] In addition, the appearance morphology of the prepared gel material P1 is shown in Figure 1 The gelling material P1 was subjected to XRD testing, and the test results are shown in Figure 2 As shown by Figure 2It can be seen that there are a lot of amorphous substances in the gel material P1, which is inferred to be gel based on the reaction product. At the same time, there are a few diffraction peaks that cannot be distinguished, which may be products containing sodium. The SEM test of the gel material P1 is as follows Figure 3 shown by Figure 3 It can be seen that the interior of the cementitious material P1 is a layered structure, and the plate structure of small particles can be clearly seen after magnification.
[0060] Example 2: Discussion on types of retarders
[0061] In order to study the influence of the type of calcium silicate mineral on the properties of the prepared cementitious material, the present invention carried out Examples 2-1 to 2-3. The specific contents of Examples 2-1 to 2-3 are as follows:
[0062] Example 2-1:
[0063] An oxalic acid-activated calcium silicate mineral cementitious material composition, consisting of oxalic acid dihydrate (48g), a calcium silicate mineral (40g) and a retarder (12g); wherein the mass ratio of the oxalic acid dihydrate to the calcium silicate mineral is 1.2:1, the particle size of the oxalic acid dihydrate is less than 100μm, and the calcium silicate mineral is γ-dicalcium silicate (particle size less than 100μm); the mass ratio of the retarder to the oxalic acid dihydrate is 1:4, the particle size of the retarder is less than 100μm, and the retarder is potassium oxalate.
[0064] The preparation method of the gamma-dicalcium silicate is as follows: silicon dioxide and calcium hydroxide are mixed in a molar ratio of 1:2, and then sintered at 1450° C. for 4 hours to obtain a sintered material; the sintered material is cooled and then ball-milled to obtain gamma-dicalcium silicate with a particle size of less than 100 μm.
[0065] The preparation method of the oxalic acid activated calcium silicate mineral cementitious material composition is as follows: weigh oxalic acid, calcium silicate mineral and retarder, and mix them evenly to obtain the oxalic acid activated calcium silicate mineral cementitious material composition.
[0066] Example 2-2:
[0067] Example 2-2 is substantially the same as Example 2-1, except that the retarder is acetic acid.
[0068] Embodiment 2-3:
[0069] Example 2-3 is substantially the same as Example 2-1, except that the retarder is citric acid.
[0070] In order to study the performance of the oxalic acid-activated calcium silicate mineral cementitious material compositions prepared in Examples 2-1 to 2-3, the oxalic acid-activated calcium silicate mineral cementitious material compositions prepared in Examples 2-1 to 2-3 were used to prepare cementitious materials, and the obtained cementitious materials were respectively recorded as cementitious material P5, cementitious material P6, and cementitious material P7. The performance of cementitious materials P5 to P7 was tested and compared with cementitious material P1. The results are shown in Table 2.
[0071] The preparation method of the cementitious material is the same as that of Example 1, and only the cementitious material composition is replaced accordingly, which will not be described in detail. The detection method of the cementitious material performance is the same as that of Example 1.
[0072] Table 2 Effect of retarder types on the properties of cementitious materials
[0073]
[0074] It can be seen from Table 2 that when acetic acid and citric acid are used as retarders, the setting time of the prepared cementitious material is relatively short, and when sodium oxalate and potassium oxalate are used as retarders, the setting time of the cementitious material reaches more than 30 minutes, and the compressive strength of the cementitious material after setting is relatively high. This shows that the type of retarder has an impact on the setting time and strength of the prepared cementitious material. In the actual construction process, the retarder can be reasonably selected according to the setting time and strength requirements of the cementitious material.
[0075] Example 3: Discussion on the mass ratio of retarder to oxalic acid
[0076] In order to study the effect of the mass ratio of retarder to oxalic acid on the properties of the prepared cementitious material, the present invention carried out Examples 3-1 to 3-4. The specific contents of Examples 3-1 to 3-4 are as follows:
[0077] Example 3-1:
[0078] An oxalic acid-activated calcium silicate mineral cementitious material composition, consisting of oxalic acid dihydrate (48g), a calcium silicate mineral (40g) and a retarder; wherein the mass ratio of the oxalic acid dihydrate to the calcium silicate mineral is 1.2:1, the particle size of the oxalic acid dihydrate is less than 100μm, and the calcium silicate mineral is γ-dicalcium silicate (particle size less than 100μm); the mass ratio of the retarder to the oxalic acid dihydrate is 3:16, the particle size of the retarder is less than 100μm, and the retarder is sodium oxalate.
[0079] The preparation method of the gamma-dicalcium silicate is as follows: silicon dioxide and calcium hydroxide are mixed in a molar ratio of 1:2, and then sintered at 1450° C. for 4 hours to obtain a sintered material; the sintered material is cooled and then ball-milled to obtain gamma-dicalcium silicate with a particle size of less than 100 μm.
[0080] The preparation method of the oxalic acid activated calcium silicate mineral cementitious material composition is as follows: weigh oxalic acid, calcium silicate mineral and retarder, and mix them evenly to obtain the oxalic acid activated calcium silicate mineral cementitious material composition.
[0081] Example 3-2:
[0082] Example 3-2 is substantially the same as Example 3-1, except that the mass ratio of the retarder to oxalic acid dihydrate is 1:8.
[0083] Example 3-3:
[0084] Example 3-3 is substantially the same as Example 3-1, except that the mass ratio of the retarder to oxalic acid dihydrate is 1:16.
[0085] Embodiment 3-4:
[0086] Example 3-4 is substantially the same as Example 3-1, except that the cementitious material composition does not contain a retarder.
[0087] In order to study the performance of the oxalic acid-activated calcium silicate mineral cementitious material compositions prepared in Examples 3-1 to 3-4, the oxalic acid-activated calcium silicate mineral cementitious material compositions prepared in Examples 3-1 to 3-4 were used to prepare cementitious materials, and the obtained cementitious materials were respectively recorded as cementitious material P8, cementitious material P9, cementitious material P10, and cementitious material P11. The performance of cementitious materials P8 to P11 was tested and compared with cementitious material P1. The results are shown in Table 3.
[0088] The preparation method of the cementitious material is the same as that of Example 1, and only the cementitious material composition is replaced accordingly, which will not be described in detail. The detection method of the cementitious material performance is the same as that of Example 1.
[0089] Table 3 Effect of the mass ratio of retarder to oxalic acid on the properties of cementitious materials
[0090]
[0091] As shown in Table 3, the addition of retarder has a prolonged effect on the setting time of cementitious materials; when the proportion of retarder in the cementitious material composition is low, the setting time of the cementitious material is short, and the early strength of the cementitious material after setting is high, which is beneficial in construction that requires rapid hardening; as the proportion of retarder in the cementitious material composition increases, the setting time of the cementitious material is gradually prolonged, and the early strength after setting decreases slightly, but the long-term strength (7d, 28d strength) is high. Therefore, in the actual construction process, the mass ratio of retarder to oxalic acid can be reasonably selected according to the setting time and strength requirements of the cementitious material.
[0092] Example 4: Discussion on water temperature for preparing cementitious materials
[0093] In order to study the effect of the mass ratio of retarder to oxalic acid on the properties of the prepared cementitious material, the present invention carried out Examples 4-1 to 4-6. The specific contents of Examples 4-1 to 4-6 are as follows:
[0094] Example 4-1:
[0095] A method for preparing a cementitious material is as follows: adding water at 5°C to the cementitious material composition described in Example 1-1, with a mass ratio of water to the cementitious material composition being 0.3:1, stirring and mixing to obtain a slurry, pouring the slurry into a 20mm*20mm*20mm six-piece mold, vibrating on a vibration table for 30s to form, scraping the upper part flat, and putting it into a curing box for constant temperature curing at 25°C to obtain a cementitious material (referred to as cementitious material P12).
[0096] Example 4-2:
[0097] The content of Example 4-2 is basically the same as that of Example 4-1, except that the water temperature used in preparing the cementitious material is 10°C; that is, 10°C water is added to the cementitious material composition described in Example 1-1, and the prepared cementitious material is recorded as cementitious material P13.
[0098] Example 4-3:
[0099] The content of Example 4-3 is basically the same as that of Example 4-1, except that the water temperature used in preparing the cementitious material is 15°C; that is, 15°C water is added to the cementitious material composition described in Example 1-1, and the prepared cementitious material is recorded as cementitious material P14.
[0100] Example 4-4:
[0101] The content of Example 4-4 is basically the same as that of Example 4-1, except that the water temperature used in preparing the cementitious material is 20°C; that is, 20°C water is added to the cementitious material composition described in Example 1-1, and the prepared cementitious material is recorded as cementitious material P15.
[0102] Embodiment 4-5:
[0103] The content of Example 4-5 is basically the same as Example 4-1, except that the water temperature used in preparing the cementitious material is 25°C; that is, 25°C water is added to the cementitious material composition described in Example 1-1, and the prepared cementitious material is recorded as cementitious material P16.
[0104] Embodiment 4-6:
[0105] The content of Example 4-6 is basically the same as that of Example 4-1, except that the cementitious material composition used in preparing the cementitious material is the cementitious material composition prepared in Example 3-4, and the water temperature used is 25°C; that is, 25°C water is added to the cementitious material composition described in Example 3-4, and the prepared cementitious material is recorded as cementitious material P17.
[0106] The properties of cementitious materials P12 to P17 were tested according to the method described in Example 1 and compared with cementitious material P1. The results are shown in Table 4.
[0107] Table 4 Effect of water temperature on the performance of cementitious materials
[0108]
[0109] It can be seen from Table 4 that when preparing cementitious materials, the water temperature has a significant effect on the setting time of cementitious materials. When the water temperature is low, the setting time of cementitious materials is relatively long, the cementitious materials react fully, and the long-term strength (7d and 28d strength) of the cementitious materials after setting is high (the highest reaches 45.4MPa); as the water temperature increases, the setting time of cementitious materials is shortened, and the early strength of the prepared cementitious materials is relatively high.
[0110] Example 5: Discussion on curing temperature when preparing cementitious materials
[0111] In order to study the effect of the curing temperature during the preparation of the cementitious material on the performance of the prepared cementitious material, the present invention carried out Examples 5-1 to 5-5. The specific contents of Examples 5-1 to 5-5 are as follows:
[0112] Example 5-1:
[0113] A method for preparing a cementitious material is as follows: adding water at 0°C to the cementitious material composition described in Example 1-1, with a mass ratio of water to the cementitious material composition being 0.3:1, stirring and mixing to obtain a slurry, pouring the slurry into a 20mm*20mm*20mm six-piece mold, vibrating on a vibration table for 30 seconds to form, flattening the upper part, and placing the mold in a curing box for constant temperature curing at 0°C to obtain a cementitious material (referred to as cementitious material P18).
[0114] Example 5-2:
[0115] The content of Example 5-2 is basically the same as that of Example 5-1, except that the curing temperature of the cementitious material is 5°C, that is, the slurry is poured into a 20mm*20mm*20mm six-piece mold, vibrated on a vibration table for 30 seconds to form, the upper part is scraped flat, and placed in a curing box for constant temperature curing at 5°C to obtain the cementitious material (recorded as cementitious material P19).
[0116] Example 5-3:
[0117] The content of Example 5-3 is basically the same as that of Example 5-1, except that the curing temperature of the cementitious material is 10°C, that is, the slurry is poured into a six-piece mold of 20mm*20mm*20mm, vibrated on a vibration table for 30 seconds to form, the upper part is scraped flat, and placed in a curing box for constant temperature curing at 10°C to obtain the cementitious material (referred to as cementitious material P20).
[0118] Example 5-4:
[0119] The content of Example 5-4 is basically the same as that of Example 5-1, except that the curing temperature of the cementitious material is 15°C, that is, the slurry is poured into a 20mm*20mm*20mm six-piece mold, vibrated on a vibration table for 30 seconds to form, the upper part is scraped flat, and placed in a curing box for constant temperature curing at 10°C to obtain the cementitious material (recorded as cementitious material P21).
[0120] Example 5-5:
[0121] The content of Example 5-5 is basically the same as that of Example 5-1, with the difference being that the curing temperature of the cementitious material is 20°C, that is, the slurry is poured into a six-piece mold of 20mm*20mm*20mm, vibrated on a vibration table for 30 seconds to form, the upper part is scraped flat, and placed in a curing box for constant temperature curing at 20°C to obtain the cementitious material (recorded as cementitious material P22).
[0122] The properties of cementitious materials P18 to P22 were tested according to the method described in Example 1 and compared with cementitious material P1. The results are shown in Table 5.
[0123] Table 5 Effect of water temperature on the performance of cementitious materials
[0124]
[0125] It can be seen from Table 5 that when preparing cementitious materials, different curing temperatures will affect the setting time and strength of cementitious materials. When cured at 0°C, the setting time can be extended to 90.4 minutes, but the early strength is low. After 7 days of curing or longer, the strength is higher (up to 55.5 MPa); moreover, as the curing temperature increases, the setting time of the cementitious material gradually shortens, the early strength of the cementitious material gradually increases, and the long-term strength decreases slightly. This shows that the cementitious material composition of the present invention can be used in a low temperature environment (0°C).
[0126] Example 6: Discussion on water-to-solid ratio of cementitious materials
[0127] In order to study the effect of the water-solid ratio on the performance of the prepared cementitious material, the present invention carried out Examples 6-1 and 6-2. The specific contents of Examples 6-1 and 6-2 are as follows:
[0128] Example 6-1:
[0129] A method for preparing a cementitious material is as follows: adding water at 0°C to the cementitious material composition described in Example 1-1, with a mass ratio of water to the cementitious material composition being 0.25:1, stirring and mixing to obtain a slurry, pouring the slurry into a 20mm*20mm*20mm six-piece mold, vibrating on a vibration table for 30s to form, scraping the upper part flat, and putting it into a curing box for constant temperature curing at 25°C to obtain a cementitious material (referred to as cementitious material P23).
[0130] Example 6-2:
[0131] The content of Example 6-2 is basically the same as that of Example 6-1, except that the mass ratio of water to the cementitious material composition is 0.35:1, that is, the slurry is poured into a 20mm*20mm*20mm six-piece mold, vibrated on a vibration table for 30 seconds to form, the upper part is scraped flat, and placed in a curing box for constant temperature curing at 10°C to obtain a cementitious material (referred to as cementitious material P24).
[0132] The properties of cementitious materials P23-P24 were tested according to the method described in Example 1 and compared with cementitious material P1. The results are shown in Table 6.
[0133] Table 6 Effect of water-solid ratio on the performance of cementitious materials
[0134]
[0135] It can be seen from Table 6 that when preparing cementitious materials, different water-to-solid ratios have little effect on the setting time of cementitious materials, but have a certain effect on the long-term strength of cementitious materials. When the water-to-solid ratio is 0.3:1 and 0.35:1, the long-term strength of the cementitious materials is higher.
[0136] Embodiment 7:
[0137] An oxalic acid-activated calcium silicate mineral cementitious material composition consists of oxalic acid dihydrate (52g), a calcium silicate mineral (40g) and a retarder (12g); wherein the particle size of the oxalic acid dihydrate is less than 100μm, the calcium silicate mineral is γ-dicalcium silicate (particle size is less than 100μm); the particle size of the retarder is less than 100μm, and the retarder is sodium oxalate.
[0138] Add 0°C water to the above-mentioned cementitious material composition, the mass ratio of water to cementitious material composition is 0.3:1, stir and mix to obtain slurry, pour the slurry into a 20mm*20mm*20mm six-piece mold, vibrate on a vibration table for 30s to form, scrape the upper part flat, put it into a curing box for constant temperature curing at 25°C, and obtain the cementitious material. The setting time is calculated from the start time of the cementitious material molding to the hardening of the cementitious material. After testing, its setting time is 31.3min. According to GB / T 50081-2019 standard, the mechanical properties of the cementitious material after solidification were tested using a pressure testing machine. The compressive strength was 6.8 MPa 5 hours after solidification, 18.9 MPa 10 hours after solidification, 32.8 MPa 1 day after solidification, 44.8 MPa 3 days after solidification, 43.1 MPa 7 days after solidification, and 44.5 MPa 28 days after solidification.
[0139] Embodiment 8:
[0140] An oxalic acid-activated calcium silicate mineral cementitious material composition consists of oxalic acid dihydrate (56g), a calcium silicate mineral (40g) and a retarder (12g); wherein the particle size of the oxalic acid dihydrate is less than 100μm, the calcium silicate mineral is γ-dicalcium silicate (particle size is less than 100μm); the particle size of the retarder is less than 100μm, and the retarder is sodium oxalate.
[0141] Add 0°C water to the above-mentioned cementitious material composition, the mass ratio of water to cementitious material composition is 0.3:1, stir and mix to obtain slurry, pour the slurry into a 20mm*20mm*20mm six-piece mold, vibrate on a vibration table for 30s to form, scrape the upper part flat, put it into a curing box for constant temperature curing at 25°C, and obtain the cementitious material. The setting time is calculated from the start time of the cementitious material molding to the hardening of the cementitious material. After testing, its setting time is 32.5min. According to GB / T 50081-2019 standard, the mechanical properties of the cementitious material after solidification were tested using a pressure testing machine. The compressive strength was 7.7 MPa 5 hours after solidification, 19.6 MPa 10 hours after solidification, 31.4 MPa 1 day after solidification, 42.6 MPa 3 days after solidification, 42.9 MPa 7 days after solidification, and 43.1 MPa 28 days after solidification.
[0142] Embodiment 9:
[0143] An oxalic acid-activated calcium silicate mineral cementitious material composition consists of oxalic acid dihydrate (60g), a calcium silicate mineral (40g) and a retarder (12g); wherein the particle size of the oxalic acid dihydrate is less than 100μm, the calcium silicate mineral is γ-dicalcium silicate (particle size is less than 100μm); the particle size of the retarder is less than 100μm, and the retarder is sodium oxalate.
[0144] Add 0°C water to the above-mentioned cementitious material composition, the mass ratio of water to cementitious material composition is 0.3:1, stir and mix to obtain slurry, pour the slurry into a 20mm*20mm*20mm six-piece mold, vibrate on a vibration table for 30s to form, scrape the upper part flat, put it into a curing box for constant temperature curing at 25°C, and obtain the cementitious material. The setting time is calculated from the start time of the cementitious material molding to the hardening of the cementitious material. After testing, its setting time is 33.3min. According to GB / T 50081-2019 standard, the mechanical properties of the cementitious material after solidification were tested using a pressure testing machine. The compressive strength was 8.1 MPa 5 hours after solidification, 20.5 MPa 10 hours after solidification, 30.9 MPa 1 day after solidification, 40.3 MPa 3 days after solidification, 42.4 MPa 7 days after solidification, and 45.1 MPa 28 days after solidification.
[0145] Finally, it should be noted that the above embodiments are only preferred embodiments of the present invention, and are not intended to limit the present invention in other forms. Any technician familiar with the profession may use the above technical content as inspiration to make changes or modifications. This is an equivalent embodiment of equivalent changes. However, any simple modification, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the technical concept of the present invention still fall within the scope of protection of the claims of the present invention.
Claims
1. An oxalic acid activated calcium silicate mineral cementitious material composition, characterized in that: Including the following ingredients: Oxalic acid, calcium silicate mineral and retarder, wherein the mass ratio of the oxalic acid to the calcium silicate mineral is (1.2-1.5):1, and the mass ratio of the retarder to the oxalic acid is (0-1):(4-5).
2. The cementitious material composition according to claim 1, characterized in that: The calcium silicate mineral is at least one of tricalcium disilicate, γ-dicalcium silicate and calcium silicate.
3. The cementitious material composition according to claim 2, characterized in that: The preparation method of the γ-dicalcium silicate is: mixing silicon dioxide and calcium hydroxide in a molar ratio of 1:2 and sintering at 1450°C; the preparation method of the tricalcium disilicate is: mixing calcium carbonate and silicon dioxide in a molar ratio of 3:2 and sintering at 1460°C.
4. The cementitious material composition according to any one of claims 1 to 3, characterized in that: The oxalic acid is anhydrous oxalic acid or / and hydrated oxalic acid; the retarder is at least one of oxalate, acetic acid and citric acid.
5. The cementitious material composition according to claim 4, characterized in that: The hydrated oxalic acid is monohydrated oxalic acid or / and dihydrated oxalic acid; the oxalate is sodium oxalate or / and potassium oxalate; the particle size of the calcium silicate mineral is ≤100 μm, the particle size of the oxalic acid is ≤100 μm; and the particle size of the retarder is ≤100 μm.
6. Use of the cementitious material composition according to any one of claims 1 to 5 in cementitious materials or concrete.
7. The method for using the gelling material composition according to any one of claims 1 to 5, characterized in that: include: The water and the cementitious material composition are uniformly mixed in proportion to obtain slurry; the slurry is subjected to molding and curing treatment to obtain a cementitious material solid.
8. The method of use according to claim 8, characterized in that: The mass ratio of the water to the cementitious material composition is (0.2-0.4):1; the temperature of the water is 0°C-25°C, and the temperature of the curing treatment is 0°C-25°C.
9. A gelling material, characterized in that: The gelling material comprises the gelling material composition according to any one of claims 1 to 5.
10. A concrete, characterized in that: The concrete comprises the cementitious material composition according to any one of claims 1 to 5.
Citation Information
Patent Citations
Magnesium-base oxalate cement
CN107098612A